Implementasi PHBS Siswa Kelas Atas di SDN 2 Pesaren - FARIS SYAFIQ AZHARUDIN; Lulu April Farida (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this research is to determine how the implementation of the behavior of clean and healthy living upper grade students in SD N2 Pesaren, as an effort to prevent virus infection covid-19. Descriptive quantitative research with survey method, and data collection using the questionnaire, where respondents are the parents/ guardians of students who see firsthand and know the activity of the student. Sample used using total sampling technique with the number of respondents as many as 51 people. Data analysis using the software SPSS version 26 and microsoft excel 2010 with the techniques of quantitative analysis with descriptive presentation of the data the results of the research shaped the percentage. The results showed that in SD Negeri 2 Pesaren, the implementation of the child's behavior class above (IV, V, VI) to a Clean and Healthy Life is mostly good, with a percentage of 78%. most of the classified as very good by 12%, in the category of Pretty by 10% and less at 0%. Based on these results it can be concluded that the application of Clean and Healthy Behavior in Children Aged Upper Class in the Elementary School 2 Pesaren is better. With the results of more than half of the sample to apply the clean and healthy behavior with good category. But thus thou proud moment, and should continue to improve the behavior of clean and healthy life so that the immunity of the body increases and protected from virus infection.